Dinámica de crecimiento de siete especies forestales de la quinta y sexta fase de la colección de Universidad Técnica Estatal de Quevedo, Provincia De Los Ríos, Ecuador - Jiménez Orellana, Xavier Wilfrido (2016)
This investigation project was carried out with the objective of evaluating the dynamics of growth of seven forest species of the fifth and sixth phase of the Collection of the State Technical University of Quevedo (UTEQ). The Collection was established in the experimental property "La Represa" of the UTEQ, in the enclosure Fayta, parish San Carlos, Quevedo canton. The species are planted at a distance of 3 x 3 m, in experimental parcels of 15 x 15 m (225 m2), established under a design of blocks at random with two repetitions. In each parcel the diameter and the height of the 9 central trees were measured, of the seven species studied in this project. With the data obtained it was proceeded to calculate the basal area, the volume and the IMA of the variable dasométricas of the seven species. The results demonstrate that the four species of the fifth phase didn't present significant differences for none of the variable studied dasométricas. The three species of the sixth phase presented significant differences for all the studied variables; the species with more average was Virola reidii (chalviande), with 18,05 cm in DAP, 11,42 m in total height, 0,0261 m2 in basal area and 0,1974 m3 in volume. The species with smaller average, of the mentioned variables, was Syzygium jambos (pomarrosa), with 9,78 cm in DAP, 5,88 m in total height, 0,0084 m2 in basal area and 0,0335 m3 in volume. Inside the species of the fifth phase, the biggest value in the medium annual increment (IMA) of the studied variables was for Cupania cinérea (come pava) with 1,35 cm in DAP; 1,27 m in total height, 0,0016 m2 in basal area and 0,0134 m3 in volume, and that of smaller value in IMA was for Cedrela odorata (cedro) with 1,07 m in DAP, 0,91 m total height, 0,0012 m2 in basal area and 0,0076 m3 in volume. In the sixth phase, the biggest value in the IMA of the studied variables was for V. reidii with 2,01 cm in DAP, 1,27 m in total height, 0,0029 m2 in basal area and 0,0219 m3 in volume. The smallest value in the IMA was for S. jambos, with 0,96 cm in DAP, 0,63 m in total height, 0,0007 m2 in basal area, and 0,0027 m3 in volume.